VCAM-1+ macrophages guide the homing of HSPCs to a vascular niche. (6th December 2018) - Li, Dantong; Xue, Wenzhi; Li, Mei; Dong, Mei; Wang, Jianwei; Wang, Xianda; Li, Xiyue; Chen, Kai; Zhang, Wenjuan; Wu, Shuang; Zhang, Yingqi; Gao, Lei; et al.
Abstract Haematopoietic stem and progenitor cells (HSPCs) give rise to all blood lineages that support the entire lifespan of vertebrates1 . After HSPCs emerge from endothelial cells within the developing dorsal aorta, homing allows the nascent cells to anchor in their niches for further expansion and differentiation2–5 . Unique niche microenvironments, composed of various blood vessels as units of microcirculation and other niche components such as stromal cells, regulate this process6–9 . However, the detailed architecture of the microenvironment and the mechanism for the regulation of HSPC homing remain unclear. Here, using advanced live imaging and a cell-labelling system, we perform high-resolution analyses of the HSPC homing in caudal haematopoietic tissue of zebrafish (equivalent to the fetal liver in mammals), and reveal the role of the vascular architecture in the regulation of HSPC retention. We identify a VCAM-1+ macrophage-like niche cell population that patrols the inner surface of the venous plexus, interacts with HSPCs in an ITGA4-dependent manner, and directs HSPC retention. These cells, named 'usher cells', together with caudal venous capillaries and plexus, define retention hotspots within the homing microenvironment. Thus, the study provides insights into the mechanism of HSPC homing and reveals the essential role of a VCAM-1+ macrophage population with patrolling behaviour in HSPC retention. In zebrafish embryogenesis, nascent haematopoietic stem and progenitor cells (HSPCs), homing to a vascular niche for retention, are ushered by patrolling and guiding macrophages through integrin-mediated cell-cell recognition.